Penyusunan Laporan Keuangan Pada Usaha Mikro, Kecil, Dan Menengah (UMKM) Laundry Qu Berdasarkan SAK EMKM - Faradia Lativa; Fayyaz Zihni Rasyidi; Sumaryanto Sumaryanto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The aim of this study was to analyze the financial reporting process of MSMEs based on the Indonesian Accounting Standards for Small and Medium Enterprises (SAK EMKM). This study employed a qualitative approach, utilizing descriptive methods to analyze information gathered through direct observation, document analysis, and interviews. Data processing was conducted by compiling interview results, field notes, and documentation, which were then grouped, explained, and analyzed according to relevant categories. The research findings indicate that Laundry Qu has applied basic principles in financial recording, but has not yet fully met the criteria. By using and implementing SAK EMKM, the preparation of financial reports becomes more structured and informative, particularly in the recording of assets, liabilities, revenues, and expenses. This research is expected to provide a reference for other MSMEs to improve financial reporting standards and enhance accounting understanding in the small business sector.